Design for Life: The Struggle for Utopia? - Predan, Barbara (Filozofski vestnik, 2018)
The objective of this paper is to identify the structural impossibility within the potential for designing our everyday life. In other words, the goal is to make a case – through a discussion of active citizenship during the era of globalised capitalism – for the necessity of the existence of unregulated islands of design activity. The paper tries to show why focusing on everyday design – design for life – should be of much greater importance than it is now. It also shows that in order to achieve this goal, design needs thinking individuals. It needs all those whose ordinary acts are overlooked today but are already happening in everyday life and are free from market domination. The task of design lies in recognising and empowering each of us. Consequently, the role of design – as one of the key builders of our environment – lies not only in redesigning the environment in order for it to ensure the requisite empowerment of individuals, but also in establishing the conditions for creating and encouraging new functions, new ways of thinking.